Phase II study of cisplatin combined to irinotecan administered alternatingly with docetaxel in advanced non-small cell lung cancer - Charoentum C. (2014)
Objective: To assess the activity and toxicity of cisplatin and irinotecan alternating with docetaxel in patients with advanced non-small cell lung cancer (NSCLC). Material and Method: Eligibility included chemo-naïve stage IIIB with malignant effusion and stage IV NSCLC patients with measurable disease and a good performance status. Twenty-four patients were enrolled into the present study. There were 19 males and 5 females with a median age of 58.5 years and the median performance status was 1. Ninety-six percent had stage IV disease. These patients received cisplatin at 80 mg/ m2 and irinotecan at 200 mg/m2 on day 1, followed by docetaxel at 75 mg/m2 on day 22, in 6-week cycle for a maximum of 3 cycles. Results: Eight out of twenty-two evaluable patients obtained a partial response (36%). The median time to tumor progression was 6 months. The median survival time and 1-year survival rate were 10.4 months and 45% respectively. The most frequent severe toxicities were neutropenia, anemia, and diarrhea. Febrile neutropenia occurred in four patients (16%), and was the cause of treatment-related deaths in two (8%). Other nonhematologic toxicities were mild including nausea, vomiting, and skin rash. Conclusion: Alternating cisplatin and irinotecan with docetaxel, as used in the present study was feasible and demonstrated encouraging efficacy in patients with non-small cell lung cancer. However, this approach appears to be more toxic, especially in myelosuppression, than in previous reports of the sequential use of the similar agents.